Metrics for code obfuscation based on symbolic execution and N-scope complexity - Yuqiang XIAO; Yunfei GUO; Yawen WANG (网络与信息安全学报)
Code obfuscation has been well developed as mitigated endogenous security technology, to effectively resist MATE attacks (e.g.reverse engineering).And it also has important value for the reasonable metrics of code obfuscation effect.Since symbolic execution is widely used in anti-obfuscation attacks, metrics for code obfuscation resilience can refer to the efforts of generating input test set for executing all program paths.However, some adversarial techniques could reduce the symbol execution efficiency significantly based on the nested structure of the program and increase the error of the resilience reference.To solve the above problems, a metrics for code obfuscation was proposed based on symbolic execution and N-scope complexity.The obfuscation resilience was defined with symbolic execution time and obfuscation potency was defined based on the proposed N-scope complexity for better robustness in measuring the resilience of multi-nested structure programs.Furthermore, the correlation analysis of obfuscation effect was proposed and the effect was quantified by symbolic execution and control flow diagram extraction of programs.Over 4000 obfuscated programs from 3 open-sourced assemblies were evaluated with proposed metrics in the experiment, which indicated the generalization performance and practicality of the metrics.And an example of this metrics application was presented in a simulated obfuscation scenario which provided references of obfuscation technology metrics and obfuscation configuration for obfuscation users.